Proposta de uma ontologia para o gerenciamento de objetos de aprendizagem - Silva, Maria das Graças Pereira da (Universidade Federal Rural do Semi-Árido, 2017)
Learning objects are increasingly present in the educational context. When they are successful as a great allies of the educational process. It is necessary for the teacher to be clear about the goals he wants to achieve and then to research, select and define good strategies for using the learning objects in his classes in order to meet his educational objectives. To facilitate reuse, learning objects must be available in a machine-readable format. To facilitate the search, use and reuse, semantic models, such as ontologies, can be used. Ontologies aim to develop a set of rules that allow inference so that the machine can, through access to these rules, abstract a semantic meaning from the information available. In this way, the present work presents an ontology for the management of learning objects, based on educational objectives, according to the cognitive domain of Bloom Taxonomy. The methodological procedure adopted to build the ontology was performed in four stages: a detailed study of the process of ontology development, the functioning of the ontology editor, and the study of pedagogical tools. Contents Map and Map of Dependencies and educational objectives of the Bloom Taxonomy ; elaboration of the document specifying ontology requirements and competence issues; definition of classes and their hierarchy, properties and instances; the validation of the ontology. The implementation of the ontology was done in the Protégé editor with the use of the OWL language. The validation was done theoretically by using hypothetical scenarios of a discipline. Given the results presented: automate the process of knowledge inference; determine the educational purpose of a student, content, and learning objects; work the contents hierarchically, and; indicate the learning objects to achieve a particular educational goal, it is considered that the use of ontologies offers a potential to be explored to improve the teaching and learning process
Keywords: Ontologia; Objetos de aprendizagem; Objetivo educacional; Ontology; Learning object; Learning goal; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO